Longevidade diferencial de fêmeas adultas de Apis mellifera - Capodifoglio, Andresa Raquel (Universidade Federal de São Carlos, 2023)
Adult females of Apis mellifera bee species exhibit variation in their longevity, with queens and laying workers (such as anarchists, pseudo queens, and queenless/orphaned workers) living longer than non-laying workers, indicating a relationship with reproductive aspects. In this study, we conducted a literature-based survey to identify potential factors associated with differences in life expectancy between these phenotypes. For queens, we observed that longevity of approximately two years is associated with oxidative processes, vitellogenin production, intestinal microbiota composition, immunosenescence, lipid composition of membranes, telomerase activity, and exclusive feeding of royal jelly. However, no data were found to explain longevity in laying workers. Therefore, we analyzed comparative gene expression data between laying and non-laying workers to identify potential marker genes for longevity. We found that non-laying workers showed higher expression of genes related to xenobiotic resistance, while pseudo queens had more abundant and preferentially expressed genes involved in the regulation of ecdysteroid hormones. Paradoxically, some candidate genes for longevity markers in queens showed opposite gene expression profiles in all phenotypes of worker layers. Based on these findings and using non-laying workers as a reference, we suggest that the mechanisms associated with greater longevity in queens do not overlap with those associated with greater longevity in laying workers.
Differential longevity of adult female Apis mellifera
Keywords: Apis mellifera; Longevidade; Eussocialidade; Casta; Revisão bibliográfica; CIENCIAS BIOLOGICAS::GENETICA